Pelatihan Budidaya Maggot BSF Sebagai Solusi Penanganan Sampah Organik Dan Pakan Ternak Di Desa Cibinong - Atmaja, Noorulviah Beredhawati; Saepudin, Ahmad; Supriadi, Cucu; Aprilia, Sri (ADINDAMAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
Cibinong Village has quite a variety of potentials, one of which is in the livestock sector. In the livestock sector, there are actors cultivating chicken, catfish, catfish and other consumption fish. One of the problems that farmers often face is the increase in the price of animal feed, fish and chicken consumed require a lot of animal feed before it can be harvested. With the high demand for animal feed, the increase in the price of animal feed has become an obstacle to the sustainability of the livestock business in Cibinong Village. The purpose of this PKM is to provide BSF Maggot Cultivation Training as a Solution for Handling Organic Waste and Animal Feed in Cibinong Jatiluhur Village, Purwakarta. The PKM method uses a socialization approach. BSF Maggot Cultivation Training as a Solution for Handling Organic Waste and Animal Feed in Cibinong Jatiluhur Purwakarta Village was carried out properly and smoothly, on February 5 2022. The people of Cibinong Jatiluhur Purwakarta Village were very enthusiastic about participating in various series of events at this BSF maggot cultivation training, because Through this training one of the community's concerns about expensive animal feed can be answered or a solution can be found. All that remains is for the people of Cibinong Jatiluhur Village, Purwakarta, to be consistent in carrying out this BSF maggot cultivation, so that the availability of animal feed can be fulfilled and the purchasing power of cheap animal feed is achieved.